1992
DOI: 10.1520/jfs13211j
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Column Procedure on Bond Elut Certify for Systematic Toxicological Analysis of Drugs in Plasma and Urine

Abstract: A single-column solid-phase extraction procedure was developed for the screening of acidic, neutral, and basic drugs from plasma. The recoveries of all 25 tested drugs exceeded 82%. After the plasma had been diluted with phosphate buffer (pH 6.0), the drugs were extracted using a single Bond Elut Certify column. The acidic and most of the neutral drugs were eluted by acetone/chloroform (1:1) and the basic drugs were eluted by 2% ammoniated ethyl acetate. Some neutral drugs appeared in both fractions. The two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 11 publications
0
15
0
3
Order By: Relevance
“…There are numerous publications on SPE for relatively clean biological samples such as plasma, serum or urine [3][4][5][6][7][8][9][10][11][12]. Until now, only a few publications have described SPE methods for whole blood [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous publications on SPE for relatively clean biological samples such as plasma, serum or urine [3][4][5][6][7][8][9][10][11][12]. Until now, only a few publications have described SPE methods for whole blood [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Suzuki et al [2] reported a rapid extraction method for some barbiturates in plasma, whole blood and urine using a Sep-Pak C18 cartridge. Chen et al [3] developed a systematic extraction method for drugs in plasma and urine using a Bond Elut Certify column.…”
Section: Discussionmentioning
confidence: 99%
“…When a Bond Elut Certify column was used for extraction, the procedure reported by Chen et al [3] was used.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, the initial dilution was increased twofold (method B) to modify the contact time between the analyte and the extraction sorbent. Dilution of the sample is also a common procedure for reducing the protein binding problem [18][19][20]. On MP3-plus, with this method, the retention ratio was 8 % higher than with method A (retention ratio = 61.8 %, RSD = 5.2 %; n = 6).…”
Section: Preparation Of the Serummentioning
confidence: 94%